Bibliometric Analysis of Agricultural Productivity - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
This study aims to map and analyze the intellectual structure and research trends of agricultural productivity through a bibliometric approach using the Scopus database and VOSviewer visualization techniques. The analysis explores keyword co-occurrence, overlay visualization, and density mapping to identify dominant themes, temporal evolution, and emerging research directions within the field. The findings indicate that agricultural productivity research is shaped by interconnected domains, including agronomic management, plant physiology, environmental sustainability, and digital agriculture technologies. Core themes such as soil fertility, crop production, and sustainable development remain highly influential, reflecting the continued importance of ecological resource management. Temporal analysis reveals a transition from traditional biological and nutrient-based studies toward contemporary topics such as machine learning, precision agriculture, and climate change adaptation. Density patterns further show that while conventional agronomic research still dominates the field, technological innovation is becoming increasingly prominent, signaling a shift toward data-driven agricultural systems. The study highlights the growing need for interdisciplinary integration to address global challenges related to food security, environmental resilience, and sustainable productivity enhancement. These findings provide a comprehensive overview of the evolving research landscape and offer insights for future studies aiming to develop more adaptive and technology-oriented agricultural productivity frameworks.